Roblox as Media for Students’ Language Output in Daily Conversation - Novita Kartika Sari; A.B. Prabowo Kusumo Adi; Sukma Nur Ardini (International Journal of Research in Education, 2026)
This study investigates the use of Roblox as a medium to enhance students’ language output in daily conversation classes. The research was conducted at BBC Semarang with six students from the Dynamic Conversation class who had no prior experience using Roblox. Employing a mixed-methods design, the study combined quantitative assessment of speaking performance—covering content, pronunciation, vocabulary, and grammar—with qualitative insights from classroom observations, questionnaires, and interviews. The findings demonstrate that Roblox-based activities effectively improved students’ motivation, confidence, vocabulary, fluency, and collaboration. The interactive and task-based design of Roblox scenarios facilitated contextual language use. It supported real-time communication, aligning with the principles of the Interaction Hypothesis and Task-Based Language Teaching. Despite initial technical challenges, students reported positive experiences and increased willingness to communicate. These results highlight the potential of immersive game-based environments in supporting EFL learners’ speaking development.